IMPACT OF VAPOUR HEAT QUARANTINE TREATMENTS ON ‘SAMAR BAHISHT CHAUNSA’ AND ‘SUFAID CHAUNSA’ MANGO FRUITS DURING SIMULATED AIR SHIPMENT TO JAPAN - M. S. Shah; A. U. Malik1; A. S. Khan; M. U. Hasan; R. Anwar; A. Amjad; M. Amin; S. Ali; M. A. Bakhsh; M. Latif (Journal of Animal and Plant Sciences, 2021)
‘Samar Bahisht Chaunsa’ and ‘Sufaid Chaunsa’ are highly admired commercial mango cultivars of Pakistan in domestic and international markets. Fruit fly being a quarantine pest has become a significant barrier in mango export trade and needs specific postharvest disinfestation treatment before export to certain countries. Presently, postharvest vapour heat treatment (VHT) of mangoes at a certified facility is mandatory for export to Japan, however its impact on fruit quality have not been investigated. Hence, in two separate experiments, effect of quarantine VHT (Japanese protocol; 47°C for 25 min) was evaluated on the quality of two commercial mango cultivars. After VHT, treated and non-treated (control) fruits were kept at ambient conditions (26±3°C and 50-60% RH) till ripening. At eating ripe stage, VHT-treated ‘Samar Bahisht Chaunsa’ mango fruits exhibited significant reduction in postharvest disease incidence and showed higher concentrations of total phenolic contents, total antioxidants, carotenoids with better eating quality (taste, flavour, texture, aroma and pulp colour) as compared to untreated control fruit. ‘Samar Bahisht Chaunsa’ mango fruits showed non-significant results for physiochemical attributes such as peel colour, softness, total soluble solids (TSS), titratable acidity (TA), TSS:TA ratio and vitamin C, while more shriveling percentage was observed in non-VHT fruits. In second experiment, VHT treated ‘Sufaid Chaunsa’ fruits exhibited higher scores for peel colour, softness and total antioxidants, and reduced disease incidence and shriveling percentage with retained eating quality (taste). Non-significant results were observed for lenticel development, TSS, TA, TSS:TA ratio and phytochemicals (vitamin C, total phenolics, antioxidants and carotenoids) respectively. In conclusion, in both cultivars, VHT-treated fruits showed better ripening and organoleptic characteristics along with lower disease severity as compared to control. Thus, vapour heat treatment can be employed as safe quarantine measure for mango fruit export to Japan.
Keywords: Vapour heat treatment; Japanese protocol; Disease incidence; Phenolics; Eating quality